The ADP-binding kinase region of Ire1 directly contributes to its responsiveness to endoplasmic reticulum stress - Quynh Giang Le (Nature Portfolio, 2021)
Abstract Upon endoplasmic-reticulum (ER) stress, the ER-located transmembrane protein, Ire1, is autophosphorylated and acts as an endoribonuclease to trigger the unfolded protein response (UPR). Previous biochemical studies have shown that Ire1 exhibits strong endoribonuclease activity when its cytosolic kinase region captures ADP. Here, we asked how this event contributes to the regulation of Ire1 activity. At the beginning of this study, we obtained a luminal-domain mutant of Saccharomyces cerevisiae Ire1, deltaIdeltaIIIdeltaV/Y225H Ire1, which is deduced to be controlled by none of the luminal-side regulatory events. ER-stress responsiveness of deltaIdeltaIIIdeltaV/Y225H Ire1 was largely compromised by a further mutation on the kinase region, D797N/K799N, which allows Ire1 to be activated without capturing ADP. Therefore, in addition to the ER-luminal domain of Ire1, which monitors ER conditions, the kinase region is directly involved in the ER-stress responsiveness of Ire1. We propose that potent ER stress harms cells’ “vividness”, increasing the cytosolic ADP/ATP ratio, and eventually strongly activates Ire1. This mechanism seems to contribute to the suppression of inappropriately potent UPR under weak ER-stress conditions.